Urban Resilience in a Global Context Actors, Narratives, and Temporalities - Brantz, Dorothee; Sharma, Avi (Urban Studies, 2020)
Urban Resilience is seen by many as a tool to mitigate harm in times of extreme social, political, financial, and environmental stress. Despite its widespread usage, however, resilience is used in different ways by policy makers, activists, academics, and practitioners. Some see it as a key to unlocking a more stable and secure urban future in times of extreme global insecurity; for others, it is a neoliberal technology that marginalizes the voices of already marginal peoples. This volume moves beyond praise and critique by focusing on the actors, narratives and temporalities that define urban resilience in a global context. By exploring the past, present, and future of urban resilience, this volume unlocks the potential of this concept to build more sustainable, inclusive, and secure cities in the 21st century.